A Model of the Marketing Strategies Influencing the Decision to Purchase Eco Cars in Thailand: โมเดลกลยุทธ์การตลาดที่ส่งผลต่อการตัดสินใจซื้อรถยนต์อีโคคาร์ในประเทศไทย - Yuwadeeniwet, Nareenuch; Pathomsirikul, Yaowapa; Sriwanut, Amornrat (Journal of Applied Economics and Management Strategy, 2019)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษารูปแบบกลยุทธ์การตลาดที่ส่งผลต่อการตัดสินใจซื้อรถยนต์อีโคคาร์ในประเทศไทย ซึ่งเป็นงานวิจัยแบบผสมผสานด้วยวิธีการวิจัยเชิงปริมาณและการวิจัยเชิงคุณภาพ กลุ่มตัวอย่างที่ศึกษาได้แก่ ผู้ซื้อรถยนต์อีโคคาร์ในประเทศไทยจำนวน 780 คน โดยรวบรวมข้อมูลด้วยแบบสอบถาม การสนทนากลุ่ม และการสัมภาษณ์เชิงลึก สถิติที่ใช้ ได้แก่ การวิเคราะห์องค์ประกอบเชิงยืนยัน และการวิเคราะห์โมเดลสมการโครงสร้างผลการวิจัยพบว่าโมเดลแบบจำลองสมการโครงสร้างเชิงสาเหตุของรูปแบบกลยุทธ์การตลาดที่ส่งผลต่อการตัดสินใจซื้อรถยนต์อีโคคาร์ในประเทศไทย ในองค์ประกอบของตัวแปรแฝง มีลักษณะความสัมพันธ์รูปแบบอิทธิพล คือ 1) ตัวแปรแฝงภายนอก คือ ปัจจัยกลยุทธ์การตลาดมีอิทธิพลทางตรงต่อตัวแปรแฝงภายในที่เป็นตัวแปรตาม คือ การตัดสินใจซื้อรถยนต์อีโคคาร์ และมีอิทธิพลทางอ้อมต่อตัวแปรแฝงภายในที่เป็นตัวแปรตาม คือ การตัดสินใจซื้อรถยนต์อีโคคาร์ในประเทศไทย โดยผ่านตัวแปรแฝงภายในที่เป็นตัวแปรคั่งกลาง คือ การยอมรับนวัตกรรม 2) ตัวแปรแฝงภายนอก คือ ปัจจัยจิตวิทยามีอิทธิพลทางตรงต่อตัวแปรแฝงภายในที่เป็นตัวแปรตาม คือ การตัดสินใจซื้อรถยนต์อีโคคาร์และะมีอิทธิพลทางอ้อมต่อตัวแปรแฝงภายในที่เป็นตัวแปรตาม คือ การตัดสินใจซื้อรถยนต์อีโคคาร์ในประเทศไทยโดยผ่านตัวแปรแฝงภายในที่เป็นตัวแปรคั่งกลาง คือ การยอมรับนวัตกรรม ซึ่งโมเดลกลยุทธ์การตลาดที่ส่งผลต่อการตัดสินใจซื้อรถยนต์อีโคคาร์ มีความสอดคล้องกลมกลืนกับข้อมูลเชิงประจักษ์ในระดับดีมาก (ค่าสถิติ c2=94.37,df=84, P-value=0.18501, RMSEA=0.013, SRMR=0.0084,GFI=0.99,AGFI=0.97) คำสำคัญ: กลยุทธ์การตลาด ปัจจัยจิตวิทยา การยอมรับนวัตกรรม การตัดสินใจซื้อ รถยนต์อีโคคาร์ ABSTRACT The purpose of this research was to study a model of the marketing strategies influencing the decision to purchase eco cars in Thailand. This research was conducted using both qualitative and quantitative research methods. The samples were 780 eco car users in Thailand, and the data were collected using a questionnaire, focus group discussion, and in-depth interviews. The statistics employed in the research were confirmatory factor analysis and the structural equation model. The results revealed that the composition of the latent variables in the structural equation model for the marketing strategies influencing the purchase decision regarding eco cars in Thailand had two influential relationships. First were the external latent variables, in terms of marketing strategy factors, which had a direct influence on the internal latent variable in terms of the decision to purchase eco cars. They also had an indirect influence on the internal latent variable in terms of the decision to purchase eco cars by passing through the mediator variable-innovation acceptance. Second were the external latent variables, in terms of psychological factors, which had a direct influence on the internal latent variable in terms of the decision to purchase eco cars. They also had an indirect influence on the internal latent variable in terms of the decision to purchase eco cars by passing through the mediator variable-innovation acceptance. The constructed model of the marketing strategies influencing the purchase decisions regarding eco cars demonstrated a good fit with the empirical data (c2=94.37, df=84, P-value=0.18501, RMSEA=0.013, SRMR=0.0084, GFI=0.99, AGFI=0.97). Keywords: Marketing Strategy, Psychological Factor, Acceptance of Innovative, Purchase Decision, Eco Car